Protection of sheep against Chlamydia psittaci infection with a subcellular vaccine containing the major outer membrane protein. - Tan, T W (1990)
An outer membrane (OM) preparation from elementary bodies (EBs) of Chlamydia psittaci (ovine abortion strain) was used to vaccinate pregnant ewes in a single subcutaneous dose and was found to achieve protection after subcutaneous challenge with infectious organisms. Inactivated purified EBs used as a single-dose vaccine also gave protection. The ratio of live to dead lambs was significantly higher in the vaccinated groups (16:1 and 15:1, respectively) than in the placebo group (8:9). Polyacrylamide gel electrophoresis and immunoblotting showed that a 40-kilodalton protein was the main protein constituent of the OM preparation, and this was positively identified as the major outer membrane protein by protein microsequencing. Electron microscopy revealed that fine particulate structures on the outermost surface of the EB were also present in the OM preparation. The findings suggest that the major outer membrane protein is an important immunoprotective determinant in ovine abortion vaccines.